Stigma of Women Leadership: The Impact on Trust and Leader Effectiveness - Sutanto, Linda; Sukoco, Badri Munir; Nadia, Fiona Niska Dinda (RSF Conference Series: Business, Management and Social Sciences, 2024)
Stigma consciousness is crucial for influencing the effectiveness of female leaders, particularly in transformational leadership. Despite the increasing representation of women in the workplace, they still face significant challenges in reaching the highest organizational positions. This study explores how stigma consciousness moderates the impact of women’s transformational leadership on trust and leader effectiveness, while trust in leaders mediates these relationships. The research model in this study was analyzed using the Structural Equation Model (SEM) and the AMOS 28 software. This approach allows researchers to look at multiple complex relationships at the same time and combines regression and factor analysis to obtain a full picture of how variables interact with each other. We assessed the descriptive statistics and psychometric properties of the measurement scales using SPSS 28. Data were collected from 200 team members and subordinates of female leaders at various organizations in Indonesia. The results indicate that although women’s transformational leadership significantly enhances trust in leaders and leader effectiveness, this impact is moderated by stigma consciousness levels. High stigma consciousness weakens the positive effect of women’s transformational leadership on trust in leaders, thus reducing leadership effectiveness. Conversely, lower levels of stigma consciousness reinforce this positive effect. This finding highlight stigma consciousness as a barrier to women leaders’ trust and an obstacle to achieving leadership effectiveness. Reducing stigma consciousness is essential for the effective acceptance and recognition of women’s leadership. An inclusive, supportive environment free from stigma enables women to lead more effectively and gain greater team trust.